Natural history of bacteriuria in women with primary biliary cirrhosis and the effect of antimicrobial therapy in symptomatic and asymptomatic groups. Issue 6 (June 1995) - Butler, P; Hamilton-Miller, J M; McIntyre, N; Burroughs, A K
Abstract : Primary biliary cirrhosis (PBC) patients have an increased incidence of recurrent urinary tract infection compared with patients with other chronic liver diseases. The course of significant asymptomatic and symptomatic bacteriuria in women with PBC was evaluated: consecutive patients were screened for bacteriuria at their outpatient appointments. Bacteriuric patients who were asymptomatic (n = 21) were randomised to receive antimicrobial therapy (n = 11), or no therapy (n = 10). Bacteriuric patients who were symptomatic (n = 13) were treated. All were followed up by weekly dipslide examination of urine. The course of bacteriuria in the 13 symptomatic and 11 asymptomatic treated patients was similar in terms of the medium interval between successive infective episodes (three and four weeks respectively), the number of relapses (six and seven) and reinfections (14 and 18). Most untreated asymptomatic patients became abacteriuric spontaneously but became reinfected with a different organism during the study period. A separate group of 24 PBC patients with no previous bacteriologically proved urinary tract infection was followed weekly in a similar fashion: seven (29%) became bacteriuric for two to four weeks during a three month period. This study suggests that treatment of recurrent bacteriuric episodes in PBC patients does not alter the natural history of their infection. The long term implication of periodically infected urine in these patients is currently unknown.